The effects of long-term drainage on processes governing CO2 und CH4 fluxes on an Arctic floodplain in Siberia - Kwon, Minjung (2016)
Arctic ecosystems have acted as a carbon sink, accumulating >1000 Pg of carbon in soils. However, increasing air temperatures and associated degradation of ice-rich permafrost in the Arctic hold the potential to modify soil topography and hydrology, with significant effects on carbon cycling. This study investigates how long-term drainage modifies ecosystem properties in an Arctic floodplain in northeastern Siberia, namely plant and microbial community structures and soil temperatures, and quantifies the net effects on CO2 and CH4 fluxes. Our study site has two areas in parallel: one that has been drained since 2004 and the other that has not been manipulated. A decade-long drainage decreased the abundance of cotton sedges, and consequently, tussock-forming sedges took the dominance. In addition, drainage increased soil temperatures at shallow layers due to lower heat capacity, but lowered them at deep layers due to lower thermal conductivity. Moreover, fractions of methanogens and methanotrophs were reduced following drainage. These changes in ecosystem properties considerably affected carbon cycle processes in multiple ways: 1) shifts in vegetation weakened CO2 uptake strength, and warmer surface soils accelerated CO2 emission rates; 2) a decrease in the abundance of aerenchymatous plants, changes in soil temperatures that potentially decrease methanogenesis rates and increase CH4 oxidation rates, and reduced fractions of CH4-associated microorganisms all contributed to a strong reduction in CH4 flux rates; and 3) CO2 and CH4 flux rates in the nongrowing season were higher in the drained area by four times and 10%, respectively, although the magnitude of fluxes was lower compared to the growing season. These findings emphasize the relevance of drainage effects for predicting Arctic ecosystems response to climate change, and the importance of long-term studies that include changes in ecosystem properties that affect CO2 and CH4 fluxes.